(untitled) - Zimdahl, Robert L (Amsterdam, 2007)
This book addresses herbicides and their use as an important aspect of modern weed management,and strives to place them in an ecological framework. The roles of culture, economics, and politics in weed management are also discussed, enabeling scientists and students to understand the larger effects on society
Chiến lược quản lý dịch hại cây trồng
Keywords: Weeds,Weeds,Herbicides,Cỏ dại,Cỏ dại,Thuốc diệt cỏ; Control,Kiểm soát